Spot speed study at Jalan Tun Fuad Stephens, Kota Kinabalu in Sabah - Mohd Azizul Ladin; Amsori Muhammad Das; Jia Yung Lim; Tsu Jian Khor; Ekin Bin Arot; Chen Choon Lee; Bartholomew Kwan; Fariq Ismeth Jaimin (2018)
Spot speed study is crucial in the development of traffic and highway engineering since the data obtained from this study required for establishment of speed trends, traffic control planning, accident and geometry design. An interval of 100m long path at Jalan Tun Fuad Stephens, 88200 Kota Kinabalu in Sabah selected as the study area and peak hour is avoided to assure the accuracy of the study. The result shows 85th percentile of vehicle speed set as the speed limit. However, strengthening on law enforcement, as well as other possible and useful options, shall be taken in order to reduce the probability of accidents to happen. This study will be beneficial especially for the use of transportation planning in the nearby area.